2009
DOI: 10.1242/jeb.024349
|View full text |Cite
|
Sign up to set email alerts
|

Losing stability: tail loss and jumping in the arboreal lizardAnolis carolinensis

Abstract: SUMMARYVoluntary loss of an appendage, or autotomy, is a remarkable behavior that is widespread among many arthropods and lower vertebrates. Its immediate benefit, generally escape from a predator, is balanced by various costs, including impaired locomotor performance, reproductive success and long-term survival. Among vertebrates, autotomy is most widespread in lizards, in which tail loss has been documented in close to 100 species. Despite numerous studies of the potential costs of tail autotomy in lizards, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
109
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 39 publications
4
109
0
Order By: Relevance
“…The negative landing angles appeared to be caused by the perch striking the lizard tail upon recoil (supplementary material Movie1). We observed that when lizards jumped from rigid perches, they often dragged their tail along the perch during takeoff, as also noted in a previous study (Gillis et al, 2009). When jumping from compliant perches, the part of the tail that was still in contact with (or sometimes above) the perch was struck when the perch recoiled, thus lifting the tail and ultimately changing the body position of the lizard during flight and landing (Fig.3A).…”
Section: Laboratory Trialssupporting
confidence: 88%
See 2 more Smart Citations
“…The negative landing angles appeared to be caused by the perch striking the lizard tail upon recoil (supplementary material Movie1). We observed that when lizards jumped from rigid perches, they often dragged their tail along the perch during takeoff, as also noted in a previous study (Gillis et al, 2009). When jumping from compliant perches, the part of the tail that was still in contact with (or sometimes above) the perch was struck when the perch recoiled, thus lifting the tail and ultimately changing the body position of the lizard during flight and landing (Fig.3A).…”
Section: Laboratory Trialssupporting
confidence: 88%
“…Lizards jumped from the rigid perch with the same general kinematics as seen in other studies (Bels et al, 1992;Gillis et al, 2009): the jump started with placement of the hind feet towards the front of the body; lizards then used their hind limbs to propel themselves forward with a mean positive body angle of 12.1±1.7deg and a mean speed and duration of 130.4±2.6cms -1 and 0.1±0s. After the takeoff phase, the aerial phase followed with the forelimbs limbs tucked close to the body, and lizards landed with the body angled so that the hind feet contacted the landing substrate first (26.7±4.2deg), at a mean distance of 34.4±0.9cm.…”
Section: Laboratory Trialsmentioning
confidence: 84%
See 1 more Smart Citation
“…Besides adjusting the centre of mass (CoM) close to the vector of propulsive thrust at take-off to avoid later body rotation [7,8], some jumpers actively use dynamic control for in-air stability. Two mechanisms have previously been proposed to counteract unwanted torque in the air: using the inertia of swinging appendages [9][10][11][12] and aerodynamic forces from flapping wings [6,7]. Take-off mechanisms and stability control that evolved in nature have led to significant progress in bioinspired designs for manoeuvrable jumping robots [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Lizards control their body position in midair during jumping and falling by swinging through air and interacting with takeoff surface. Studies of ground reaction forces (GRFs), moment of inertia and center of mass (CoM) in lizards before and after autotomy showed that changes in these parameters may cause negative impacts on the body dynamics during jumping and falling [48,49,52]. For example, locomotive changes (i.e., morphology, GRFs and kinematics) in Eublepharis macularius due to autotomy, resulted in 13% of anterior shift of CoM.…”
Section: Impact On Performance Due To Autotomy and Regenerated Tailmentioning
confidence: 99%